SECURING THE WORLD LOCALLY: UNVEILING CHINA'S COUNTERTERRORISM POLICY - Wicaksa, Arif; Aftah, Chairul (BHUVANA: Journal of Global Studies, 2023)
Terrorism has become a critical worldwide security concern in the aftermath of the 9/11 tragedy, provoking varying reactions from various states. This research focuses on the distinguishing features of China's counterterrorism policy. The study methodically unravels China's multifaceted perspective on terrorism through interpretative research supported by qualitative analysis. The glocalization lens sheds light on the dynamic interaction of China's local context within the larger global discourse. Within this context, terrorism within China's borders is recast as separatist, a notion intrinsically tied to China's entire understanding of the threat. China effectively turns global terrorist worries into a rationale for its region-focused counterterrorism efforts, which are localized in Xinjiang and Tibet. Furthermore, China's technique departs from Western paradigms by adding socioeconomic factors as crucial components, resulting in a complex and distinctively Chinese approach. In addition, China deliberately utilizes its Belt and Road Initiative (BRI) projects to spread its counterterrorism narrative worldwide while simultaneously legitimizing its internal measures. The paper thoroughly explains China's counterterrorism policy through this analysis to highlight the roots of its unique interpretation, localized remedies, socioeconomic integration, and global outreach strategies.